Comparative study of the effect of teicoplanin and vancomycin upon the phagocytic process of peritoneal macrophages. (Revista Española de Fisiología, 1996)
The effect of Teicoplanin and Vancomycin upon the phagocytic process was compared by evaluating the different activities of the peritoneal macrophage phagocytic function from mice treated with these antibiotics. The results indicated that teicoplanin and vancomycin increased both the substrate adherence and chemotaxis of peritoneal macrophages and that neither antibiotic, at the concentrations of 10, 25, 50, 75 and 100 mg/l, had any chemoattractant capacity for peritoneal macrophages. There was an increase in the attachment of Candida albicans only in the macrophages from mice treated with vancomycin. The phagocytosis of C. albicans, Staphylococcus aureus, Escherichia coli and inert particles as well, as the nitroblue tetrazolium reduction capacity (microbicide capacity) increased in the presence of both antibiotics. The C. albicans digestion capacity increased only in the peritoneal macrophages from mice treated with teicoplanin.